Poloxamer 407 and Hyaluronic Acid Thermosensitive Hydrogel-Encapsulated Ginsenoside Rg3 to Promote Skin Wound Healing - Peng, Xiaojuan; Ding, Chuanbo; Zhao, Yingchun; Hao, Mingqian; Liu, Wencong; Yang, Min; Xiao, Fengyan; Zheng, Yinan (Frontiers in Bioengineering and Biotechnology, 2022)
Ginsenoside Rg3 has shown beneficial effects on a variety of skin diseases, and the current interest in designing and developing hydrogels for biomedical applications continues to grow, which inspires the further development of drug-loaded hydrogels for tissue repair and localized drug delivery. Thus, the aim of the present study was to develop an effective and safe hydrogel (Rg3-Gel), by making use of ginsenoside Rg3. And evaluate the wound healing potential and therapeutic mechanism of Rg3-Gel. The results obtained indicated that optimized Rg3-Gel underwent discontinuous phase transition at low and high temperature. Rg3-Gel also exhibited good network structures, swelling water retention capacity, and sustainable release performance, and excellent biocompatibility. And then, the good antibacterial and antioxidant properties of Rg3-Gel were confirmed by vitro experiments. Rg3-Gel increases the expression of autophagy proteins by inhibiting the MAPK and NF-KB pathways in vivo. Moreover, it works simultaneously regulating host immunity by increasing the abundance of beneficial bacteria and the diversity of the wound surface flora. From these preliminary evaluations, it is possible to conclude that Rg3-Gel has excellent application potential in wound healing drug delivery systems.